2014
DOI: 10.1002/jbmr.2169
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fas and Treg Cells in Fracture Healing as Characterized in the Fas-Deficient (lpr) Mouse Model of Lupus

Abstract: Previous studies showed that loss of tumor necrosis factor α (TNFα) signaling delayed fracture healing by delaying chondrocyte apoptosis and cartilage resorption. Mechanistic studies showed that TNFα induced Fas expression within chondrocytes; however, the degree to which chondrocyte apoptosis is mediated by TNFα alone or dependent on the induction of Fas is unclear. This question was addressed by assessing fracture healing in Fas-deficient B6.MRL/Faslpr/J mice. Loss of Fas delayed cartilage resorption but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…41 Finally, in a model of SLE, in which mice have defective Fas receptors (TNF receptor superfamily member 6), the percentage of iT REG cells was increased in both callus and bone tissues during the period of active cartilage formation, while at the same time the number of activated T cells in these tissues decreased, despite increased numbers of activated T cells in the spleen, indicative of an autoimmune condition. 19 These results suggest that activated iT REG cells are chondroprotective and are consistent with studies showing that mesenchymal stem cells induce both the differentiation and immunosuppressive function of iT REG cells. 42,43 Pharmacological factors that alter immune function and inflammation might have negative and positive effects on fracture healing and are important to consider in the context of specific comorbidities that affect regeneration.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…41 Finally, in a model of SLE, in which mice have defective Fas receptors (TNF receptor superfamily member 6), the percentage of iT REG cells was increased in both callus and bone tissues during the period of active cartilage formation, while at the same time the number of activated T cells in these tissues decreased, despite increased numbers of activated T cells in the spleen, indicative of an autoimmune condition. 19 These results suggest that activated iT REG cells are chondroprotective and are consistent with studies showing that mesenchymal stem cells induce both the differentiation and immunosuppressive function of iT REG cells. 42,43 Pharmacological factors that alter immune function and inflammation might have negative and positive effects on fracture healing and are important to consider in the context of specific comorbidities that affect regeneration.…”
Section: Introductionsupporting
confidence: 90%
“…1517 Interestingly, fracture leads to suppression of the immune system, 18 with a local increase in the number of induced T regulatory (iT REG ) cells that suppress active adaptive immune responses within the fracture callus. 19 Studies have further shown that mesenchymal stem cells actively maintain a hypoimmunogenic state 20,21 through the production of immunosuppressive paracrine factors, 2224 or through the direct actions of these cells on immune-cell populations, including T cells. 25,26 Such effects suggest that these cells impart immune tolerance throughout the early stages of endochondral bone formation and provide protection to the developing tissues by suppressing allo-proliferation of T cells during stem-cell recruitment and cartilage formation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple cytokines, including interleukin (IL)‐1β, IL‐6, IL‐17, IL‐23, and tumor necrosis factor alpha (TNF‐α), are expressed at various stages and present a role in healing . This initial infiltration of immune cells is followed by a suppression of the immune system, with increased differentiation of skeletogenic mesenchymal stem cells and regulatory T (Treg) cells, both of which are capable of inhibiting adaptive T cell responses and achieve a hypoimmunogenic state at the healing site . This suppression of continued inflammation is critical to proper healing, because in the presence of unresolved immune activation, such as when a bacterial infection is present or when the patient presents a pre‐existing inflammatory condition, the catabolic osteoclasts are also highly activated, resulting in reduced accumulation of mineralized bones and delayed union or nonunion …”
Section: Introductionmentioning
confidence: 99%